PENGETAHUAN DAN PERILAKU PASIEN TUBERKULOSIS TERHADAP PENYAKIT DAN PENGOBATANNYA - Hidayah Karuniawati; Arifah Sri Wahyuni; Heni Mirawati; Suryani -; Sulistyarini - (Universitas Muhammadiyah Semarang, 2015)
Tuberculosis is the most problem in health care and leading the first death in infection disease in Indonesia. Knowledge and behavior in fluent to success in medication tbc. The purpose of this study was to understanding knowledge and behavior patient tuberculosis about their disease and medication. This study was descriptive approach, collecting data had been done by interview and questioner to patient tuberculosis, and clarification to medical record and medical staff. Result showed that respondents knowledge about their disease is 83% in high category and 17% in moderate category, respondents knowledge about their medicinal treatment is 97% in high category and 3% in moderate category. Respondents know about their disease, symptoms, and how the disease spread or infect to another, and know how to prevent spreading of this disease. Respondents know that tbc can be cured and the length of medication needs for several months. Being heal, respondents do disciplinary to taking their medication.Keywords : tbc, knowledge, behavior, disease, medication